The Importance of Principal Academic Supervision in Improving Chemistry Learning - Novalita, Lidya (PPSDP International Journal of Education, 2022)
The purpose of this study is to find out the role of academic supervision of the principal in improving the quality of chemistry learning at SMA Negeri 2 Kayuagung. The data sources in this study are the Principal and the chemistry teacher. This research use qualitative methods. Data Collection Techniques: Observation, Interview, Documentation. Data Analysis Techniques: 1) data reduction, 2) data presentation and 3) Data verification. The results showed that the principal had played a role in improving the quality of chemistrys learning through academic supervision obtained from the results of interviews with principals and chemistrys teachers at SMA Negeri 2 Kayuagung. This research has never been done before by researchers because this research that had done before only focus on the result of supervision such as productivities outcomes not quality or performance , and this research contributes to school principals to improve the work environment and motivate and improve the quality of chemistry learning.